2006
DOI: 10.1590/s0034-72992006000200015
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia da cirurgia endoscópica nasal nos sintomas da rinossinusite crônica associada ou não à polipose

Abstract: Funct ional endoscopic sinus surgery is the preferred treatment for chronic rhinosinusitis currently. Success on symptoms relief and quality of life improvement are the study leading objectives. Study design: retrospective clinical trial. Methods: Questionnaires were given to the patients referred to Hospital das Clinicas-UFPE to chronic rhinosinusitis (CRS) functional endoscopic sinus intervention during [2003][2004]. Symptoms outcome before and after surgery were compared and analyzed using a five-pointranki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Skull base surgery and revision procedures with distorted anatomy are the procedures most in need of precise anatomical references. 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Skull base surgery and revision procedures with distorted anatomy are the procedures most in need of precise anatomical references. 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…Its effects were respectively: 95.45% 86.3% 81.8% 81.2% 72.7% in patients with CRS and polyposis in the group we find: 100%, 83%, 58.3% , 100% and 91.6%. Compared with the national study conducted in 2006 at the Hospital de Clinicas, Federal University of Pernambuco (8) gives 100% nasal obstruction, headache in 87.5%, 91.6% in rhinorrhea and hyposmia in 83.3%, the which shows correlation between the incidence of symptoms. In the same study, the improvement of nasal obstruction was 92.3% in patients with nasal polyps, 76.6% in our study.…”
Section: Severity Of Symptoms Of Rhinosinusitis (Eva) 0______________mentioning
confidence: 67%
“…In the study by Damm (10) the overall improvement after surgery was 85%, while Bhattcharyya (7) described improvement in 100% of patients, especially in the following symptoms: facial pain, congestion, nasal obstruction, rhinorrhea, and headache. In a similar study conducted at University Hospital of Pernambuco (8) found an overall improvement in 50% of patients, 54.2% of cases reported considerable gain in quality of life. In the study by Dursun (11) and colleagues, which examined the predictors of success in CRS FEES, was hit success of FESS in 83% of cases, 54.4% had associated nasal polyposis.…”
Section: Severity Of Symptoms Of Rhinosinusitis (Eva) 0______________mentioning
confidence: 71%
See 2 more Smart Citations